Проект "Доброго порядка" Романа Мстиславича в свете изучения Академической рукописи второй части "Истории Российской" В.Н. Татищева - Майоров, А. (Спеціальні історичні дисципліни: питання теорії та методики, 2007)
У статті встановлюється час й обставини роботи В.М. Татищева над повідомленням про проект «доброго порядку» галицько-волинського князя Романа Мстиславича. На основі кодикологічного аналізу Академічного рукопису другої частини «Історії Російської» спростовується гіпотеза про пізнє походження цього повідомлення, начебто сфальсифікованого самим В.М. Татищевим. The article deals with the determination of the time and the circumstances of Tatishev research of the text about the project of “good order” of prince Roman Mstislavich of Galich and Volin. By the rules analysis of the codices the Academic manuscript of the second part “Histories Russian” was studied by author. The hypothesis is refused about late origin this notify and about adulterated text this notify by Tatishev.